Distance Education During COVID-19 Pandemic: A College of Pharmacy Experience - Altwaijry N; Ibrahim A; Binsuwaidan R; Alnajjar LI; Alsfouk BA; Almutairi R (Risk Management and Healthcare Policy, 2021)
Najla Altwaijry,1 Alnada Ibrahim,2,3 Reem Binsuwaidan,1 Lina I Alnajjar,2 Bshra A Alsfouk,1 Raghdah Almutairi4 1Department of Pharmaceutical Sciences, College of Pharmacy, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia; 2Department of Pharmacy Practice, College of Pharmacy, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia; 3Department of Pharmaceutics, Faculty of Pharmacy, University of Khartoum, Khartoum, Sudan; 4College of Pharmacy, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi ArabiaCorrespondence: Alnada IbrahimDepartment of Pharmacy Practice, College of Pharmacy, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi ArabiaTel +966503308360Email alnada44@hotmail.comPurpose: This study aimed at describing the experience of academic staff and students with distance education, during the COVID-19 pandemic, at a college of pharmacy in Saudi Arabia.Methods: This study used a mixed-method approach. The first phase implemented a survey that targeted both academic staff and students to evaluate their experiences with distance education during the COVID-19 pandemic. Then, a focus group discussion was conducted to explore, in-depth, their experience. The survey consisted of five domains as follows: readiness for the shift to distance education during the full and partial lockdown, perception towards distance education, barriers against distance education, and the acquisitions due to distance education. A five-point Likert scale was used to assess participants’ responses to the different domains (mean score ± standard deviation).Results: Seventy-eight percent of the academic staff and 65% of the students responded to the survey. Participants’ views were positive for readiness for the shift to distance education during the full lockdown (3.89± 0.42 for academic staff and 3.82± 0.50 for students) with almost similar evaluation for the readiness during the blended learning period (3.91± 0.44 for staff and 3.83± 0.59 for students). The findings showed a generally positive perception towards distance education (3.59± 0.67 for academic staff and 3.47± 0.64 for students). The acquisitions due to distance education were also positive (3.95± 0.72 for academic staff and 3.78± 0.77 for students). Nonetheless, some barriers that affected distance education were raised with an overall neutral view from both academic staff (3.31± 0.72) and students (3.31± 0.64), with different responses for the individual items. Qualitative findings from the focus group discussions explored the strengths, weaknesses, opportunities, and challenges, with emphasis on the areas for improvement.Conclusion: Although the shift for distance education was out of a sudden, participants showed overall positive views about their experience with distance education and highlighted areas for improvement.Keywords: Coronavirus crisis, remote education, pharmaceutical education, perception, blended learning, distance education